Pengaruh keagamaan dan iklim organisasi beretika terhadap integriti pegawai tadbir dan diplomatik - Radiaton Nizar, Muhammad Japri (2022)
The main purpose of this study is to examine the level of integrity of Administrative and Diplomatic Officers and the factors that influence their level of integrity. Two hundred ninety-four respondents participated in this study. Normality and reliability test were carried out. This study used descriptive analysis to determine the level of integrity of Administrative and Diplomatic Officers, while Pearson Correlation analysis was used to determine the relationship between the independent variables (religiosity and ethical organizational climate) and the dependent variable (integrity) of Administrative and Diplomatic Officers. To determine the influence of religiosity and ethical organizational climate on integrity, this study used regression analysis. The findings indicated that the level of integrity of Administrative and Diplomatic Officers is high. The relationship between religiosity and integrity is negative but still significant while the relationship between ethical organizational climate is significant but relatively weak. Based on the regression analysis, only ethical organizational climate is found to have a positive influence on integrity while religiosity has a negative influence on integrity. Thus, only one hypothesis is accepted. Therefore, the study recommends that to enhance the integrity of Administrative and Diplomatic Officers in Malaysia, ethical organization climate should be given high attention.